You don’t always get what you pay for: bonuses, perceived income and effort - Schnedler, Wendelin (German economic review, 2011)
Consider a principal-agent relationship in which more effort by the agent raises the likelihood of success. This paper provides conditions such that no success bonus induces the agent to exert more effort and the optimal contract is independent of success. Moreover, success bonuses may even reduce effort and thus the probability of success. The reason is that bonuses increase the perceived income of the agent and can hence reduce his willingness to exert effort. This perceived income effect has to be weighed against the incentive effect of the bonus. The tradeoff is determined by the marginal effect of effort on the success probability in relation to this probability itself (success hazard-rate of effort). The paper also discusses practical implications of the finding.
Gesehen am 12.10.2022